La teoría y metodología de la historia conceptual en Reinhart Koselleck / The Theory and Methodology of Conceptual History in Reinhart Koselleck - Cheirif Wolosky, Alejandro (Historiografías, 2017)
El presente artículo presenta una panorámica de la teoría y metodología de la historia conceptual de Reinhart Koselleck, base del conocido diccionario Geschichtliche Grundbegriffe que este autor compuso con Otto Brunner y Werner Conze. Utilizando textos en alemán e inglés inéditos en español, ponemos el acento en temas como la idea del carácter polisémico de los conceptos, el concepto de “estado de cosas”, la historia conceptual como crítica de fuentes y redefinición de la noción de anacronismo, y la distinción entre historia presente e historia pasada. En la última parte abordamos el tema central de las nociones espacio de experiencia y horizonte de expectativas. Palabras claves Koselleck, Historia conceptual, espacio de experiencia, horizonte de expectativas. Abstract In this article we shall provide an overview of the theory and methodology of Reinhart Koselleck’s conceptual history, basis of the well-known dictionary Geschichtliche Grundbegriffe this author wrote with Otto Brunner and Werner Conze. Using texts from German and English language never translated into Spanish, we emphasize topics such as the idea of the polysemic nature of concepts, the notion of a “state of things”, the idea of conceptual history understood as a critique of historical sources and as a redefinition of the notion of anachronism, and the distinction between current and past history. In the last section, it is addressed the pivotal topic of the notions space of experience and horizon of expectations. Key Words Koselleck, Conceptual history, space of experience, horizon of expectations.